2016
DOI: 10.1186/s12913-016-1583-3
|View full text |Cite
|
Sign up to set email alerts
|

“Talk with me”: perspectives on services for men with problem gambling and housing instability

Abstract: BackgroundProblem gambling and homelessness are recognized as important public health concerns that significantly impact individuals, their friends and families, communities and broader society. We aimed to explore the experiences with health and social services of men who had histories of problem gambling and housing instability in Toronto, Ontario.MethodsWe used a community-based participatory approach with a multi-service agency serving low-income individuals. We conducted qualitative interviews with men (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 49 publications
(56 reference statements)
0
41
0
Order By: Relevance
“…Those who are most susceptible to PG often experience other complex health and social concerns such as homelessness, mental health issues, substance use disorders, and incarceration [ 3 5 ]. Existing services are often not integrated and thus are not designed to address concurrent concerns with PG [ 6 ]. Among treatment seeking individuals, there is a need to increase awareness of existing PG-related services and supports [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those who are most susceptible to PG often experience other complex health and social concerns such as homelessness, mental health issues, substance use disorders, and incarceration [ 3 5 ]. Existing services are often not integrated and thus are not designed to address concurrent concerns with PG [ 6 ]. Among treatment seeking individuals, there is a need to increase awareness of existing PG-related services and supports [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Existing services are often not integrated and thus are not designed to address concurrent concerns with PG [ 6 ]. Among treatment seeking individuals, there is a need to increase awareness of existing PG-related services and supports [ 6 ]. Further, while there are PG interventions that have demonstrated effectiveness, they can be inaccessible to many vulnerable groups due to barriers such as geographical distance, long waitlists, and treatment costs [ 6 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fragmentation of services in Canada was identified by Guilcher and colleagues, who reported a lack of service integration among men living with problem gambling in an urban setting. In this qualitative study, Canadian men who were precariously housed and experiencing problem gambling reported not receiving screening or combined services for their complex needs (e.g., housing instability and substance abuse disorders) through one program (Guilcher et al, ). The authors suggested that there was a need to address the intersection of problem gambling with other complex health and social needs using an integrated care plan or a one‐stop‐shop design (Guilcher et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the obstacles, there is some evidence that prisoners are in fact keen to receive support and treatment (Riley 2017;Lind et al 2019). Given the challenges involved in identifying addiction, it is important that steps are taken within the correctional system to address the lack of knowledge and awareness about problem gambling and the lack of services in general (Guilcher et al 2016;Hamilton-Wright et al 2016).…”
mentioning
confidence: 99%